ملامح التّعايش اللّغويّ بين اللغة التعليميّة واللّهجات الجزائرية؛ دراسة معجميّة للألفاظ الحضاريّة في الكتب والمعاجم المدرسيّة: Linguistic Coexistence between Educational Language and Algerian Dialects, A lexicographical Study for civilization words in School Dictionary and Textbooks - نزار قبايلي, آمال; هدنة, خالد (Maalim, 2022)
In Algeria in particular, and in the Arab region in general, Linguistic Pluralism has added diversity to the educational language in the school environment. The linguistic strategy has changed according to the new educational reforms, in accordance with the cultural homogeneity and linguistic harmony between Arabic and local dialects, including Amazigh. From this point of view, we present this research paper, according to an analytical descriptive study, in which we want to measure the nature of this linguistic coexistence employed within the educational text for the primary school students in Algeria represented by civilized expressions according to a lexicographical view.